الموارد الترابية وتحديات التنمية المحلية بمنطقة غفساي - عبد الحق أبوسالم (جامعة سيدي محمد بن عبد الله ، كلية الآداب و العلوم الإنسانية - ظهر المهراز-، فاس, 2020)
The Ghefsay region, like the rest of Morocco, is known for its profound sociological and economic transformations, which were exacerbated when the population became a real threat to natural resources, especially after entering the cultivation of cannabis, which turned the balance of living of the citizens. Those who are interested in the developmental issue must stand on the magnitude of the delay accumulated by the Ghefsay region as far development is concerned, especially as it is considered one of the regions that has a high population density reaching 119 n / km2 according to the 2014 census, as well as a continuous increase in the population recorded in various statistical processes conducted in Morocco. What also made the high demand for land as well as the expansion of agricultural exploitation and the search for new places to live Considering this situation, we posed the following problem: To what extent will it be possible to build a sustainable and participatory territorial project, from mobilizing territorial resources in the Ghefsay region and bypassing various societal constraints and winning the stakes of local development? To answer this problem, we assumed mobilizing territorial capabilities and resources in the Ghefsay region to overcome various constraints and achieve local development based on good governance centered on a structured territorial project based on mountain tourism. Our choice of the topic "Territorial resources and local development challenges in the Ghefsay region" has been linked to a set of motivations, the most important of which are: our belonging to the region and our close acquaintance with all the field and social transformations that are taking place, and then the importance that the topic of territorial resources and its relationship to development acquire. The topic of the thesis is considered a continuation of a research project whose starting point was the research of the Master Studies. To answer the problem, we worked on adopting an integrated geographical approach based mainly on the descriptive analytical method, in which we took the following steps: literature review, access to administrative reports, and field study that included two parallel stages throughout the course of the research: - Phase of field visits الموارد الترابية وتحديات التنمية المحلية بمنطقة غفساي 4 - The stage of distributing the field form in which the case study community included the Ghafsay region, but the research sample was restricted to five local municipalities out of 13 existing in the region, based on several criteria: Selecting one municipality among others with similar natural and human characteristics, ensuring the representation of all tribes, then targeting the rural and urban settings. As for the research sample, 300 people were selected from the five municipalities according to their demographic weights. In connection with what has been said before, we focused in this research paper on analysing the most important territorial resources and on examining potential levels of its reconstruction. We finally, concluded that despite the availability of rich natural and human resources, the indicators of development remain weak and far from the aspirations of the population. Considering this analysis, we have foreseen a participatory and sustainable territorial project, which consists in mobilizing territorial resources to overcome various societal constraints and win the local development bet.
Keywords: Interface ressources, sociétés et dynamiques territoriales; الموارد الترابية; تحديات التنمية المحلية; منطقة غفساي; earth resources; local development; challenges; dirt project; forest deterioration